Determinants of tax compliance amongst UTM-JB's staff - 611528 Tee, Jackson Vui Yang, 1994- author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2017